Lectin histochemical findings of modified glycome of corneal structural components in experimental hypothyroidism - M. B. Shchur; Kh. I. Strus; A. M. Yashchenko (Ukrainian Society of Ophthalmologists, 2019)
Background: Carbohydrate determinants of the cellular surface and cytoplasmic glycopolymers which enable their mutual recognition, and effect cell proliferation, cell size and movement regulation and apoptosis, have become a focus of recent attention of researchers. Lectins have been used as specific tools in the research of carbohydrate-containing biopolymers, the letter being represented in a living organism by glycoproteins, glycolipids, and polysaccharides. Purpose: To investigate the effect of experimental hypothyroidism on the histophysiological characteristics and on the glycome of corneal structural components. Materials and Methods: A total of 35 adult male Wistar rats (weight, 180-240 g; 25 experimental rats and 10 control rats) were used in the study. Experimental hypothyroidism was induced by the addition of merkazolil at 5 mg/kg of body weight to the meals daily for two weeks. Thyroid glands and eye globes were excised and fixed with Bouin's fluid and 4% formalin. Preparations were stained with hematoxylin and eosin. Histological, general histochemical and lectin histochemical studies were conducted. Lectin histochemistry studies were performed with the use of a panel of six lectins (РNA, HPA, SNA, LABA, WGA, and CNFA). Results: We found morphological changes in the cornea of rats with experimental hypothyroidism. These changes included keratinization and local exfoliation of the surface layer of the anterior corneal epithelium, edema and lymphocyte infiltration at the site of the expanded venous sinus, local exfoliation of the anterior chamber endothelium, reduced expression of receptors of HPA and CNFA in the anterior epithelium and increased expression of receptors of these lectins in keratocytes and collagen fibrils of the corneal stroma. Accumulation of the latter may exert effects on epithelial adhesion to the basement membrane and change corneal clarity which is associated with keratocyte production of crystallines and keratan sulfates. Conclusion: We found morphological changes and modified glycome of corneal structural components in experimental hypothyroidism.